Independent factors for the development of vasoplegic syndrome in patients undergoing coronary artery bypass surgery - Palm, Constantin L.; Baumhove, Lukas; Pabst, Simon; Guenther, Ulf; Book, Malte; Chaduneli, Onise; Martens, Andreas; Mellert, Friedrich; Dewald, Oliver (Frontiers in Cardiovascular Medicine, 2024)
Objective Vasoplegic syndrome remains a common complication of cardiac surgery. It has serious implications for the healthcare system and individual patients, as it leads to rising healthcare costs and higher mortality. A better understanding of factors triggering vasoplegic syndrome is essential for the development of effective prevention strategies. We aimed to identify clinical characteristics and intraoperative parameters associated with the development of vasoplegic syndrome in coronary artery bypass graft surgery and the influence of vasoplegia on outcome. Methods We retrospectively analyzed the data of all patients who underwent isolated coronary artery bypass graft surgery or coronary artery bypass graft surgery combined with atrial appendage occlusion, using the heart-lung machine at our institution from 04/2019 to 12/2020. Vasoplegic syndrome was defined as MAP ≤60 mmHg and norepinephrine equivalence dosage of ≥0.2 μg/kg/min with a central venous saturation ≥60% within 2 days from surgery. Results Of 647 patients included in this study, 72 (11.1%) developed vasoplegic syndrome. Patients experiencing vasoplegia had longer stay in ICU, more frequently underwent tracheostomy and suffered more often from pneumonia. The duration of extracorporeal circulation, intraoperative application of platelet concentrates and usage of cold crystalloid cardioplegia (Bretschneider) independently predicted development of vasoplegic syndrome. Conclusions Even in relatively low-risk cardiac surgery, vasoplegic syndrome is a common complication and was associated with serious adverse effects. The use of warm blood cardioplegia (Calafiore) seems to be safer than cold crystalloid cardioplegia (Bretschneider) and might be preferable in patients that are vulnerable to the consequences of vasoplegic syndrome.